Prevalence of smartphone addiction and its relation with psychological distress and internet gaming disorder among medical college students - Zhang, Ming; Chi, Chenru; Liu, Qingwei; Zhang, Yuhao; Tao, Xiubin; Liu, Huan; Xuan, Bin (Frontiers in Public Health, 2024)
Background The incidence of smartphone addiction has been widely studied, but the research on the relationship between smartphone addiction and psychological distress and internet gaming disorder is limited. This study investigated the characteristics and prevalence of smartphone addiction and its relation with psychological distress and internet gaming disorder. Furthermore, it provides the scientific basis for intervention measures in schools, families, and society. Methods A random cluster sampling method was applied to investigate 656 medical students from grades 1 to 4 at Wannan Medical College in Anhui province, People’s Republic of China. The questionnaire consisted of general information, a smartphone addiction scale, an Internet gaming disorder scale, and a Kessler 6-item psychological distress test. The obtained results were first summarized using descriptive statistics. The Chi-square test was used to compare the status of smartphone addiction. Binary logistic regression was used to analyze the relationship between smartphone addiction and various variables. Results Our results showed that the prevalence of smartphone addiction in medical students was 49.5% (325/656). Psychological distress (p < 0.001), internet gaming disorder (p < 0.001), and childhood trauma (p = 0.001) were highly correlated with smartphone addiction in medical students. Psychological distress, and internet gaming disorder were positively associated with smartphone addiction (p < 0.000). Conclusion The prevalence of smartphone addiction is high among medical students in Chinese. Smartphone addiction is highly related to related to internet gaming disorder and psychological distress.